Ca2+-Sensor Neurocalcin δ and Hormone ANF Modulate ANF-RGC Activity by Diverse Pathways: Role of the Signaling Helix Domain - Duda, Teresa; Pertzev, Alexandre; Ravichandran, Sarangan; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2018)
Prototype member of the membrane guanylate cyclase family, ANF-RGC (Atrial Natriuretic Factor Receptor Guanylate Cyclase), is the physiological signal transducer of two most hypotensive hormones ANF and BNP, and of the intracellular free Ca2+. Both the hormonal and the Ca2+-modulated signals operate through a common second messenger, cyclic GMP; yet, their operational modes are divergent. The hormonal pathways originate at the extracellular domain of the guanylate cyclase; and through a cascade of structural changes in its successive domains activate its C-terminal catalytic domain (CCD). In contrast, the Ca2+-modulated pathway originates and is translated directly at the CCD via its sensor, myristoylated neurocalcin δ. Through a detailed sequential deletion and expression analyses, the present study demonstrates that segregation of the two transduction pathways occurs through the signaling helix domain (SHD). SHD is a conserved 35-amino acid helical region of the guanylate cyclase, composed of five heptads, each meant to tune and transmit the down-stream hormonal signals to the CCD for their translation and generation of cyclic GMP. Its structure is homo-dimeric with antiparallel configuration; it has no role in regulation of the Ca2+-modulated pathway. The findings establish and define in molecular terms the presence of two distinct non-overlapping transduction modes of ANF-RGC, and for the first time demonstrate how they operate, and, yet generate cyclic GMP utilizing common CCD machinery.